PENGARUH STRATEGI PEMBELAJARAN EVERYONE IS TEACHER HERE TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PAI DAN BUDI PEKERTIDI SMP N 2 SORKAM BARAT - Fitri Fauziah Pasaribu; Yelfi Dewi (CV. ADIBA ASIHA AMIRA, 2025)
This research is motivated by the strategy that is still not varied in the implementation of learning, many students who feel bored with Islamic Religious Education and Character Education learning and learning that tends to be monotonous and not synchronous at each meeting, this results in learning outcomes still below the minimum completion criteria. The purpose of this study was to determine the difference between Islamic Religious Education and Character Education learning outcomes on the subject of Believing in the Books of Allah using the Everyone Is Teacher Here strategy (experiment) and expository strategy (control) and to determine the effect of the Everyone Is Teacher Here learning strategy on student learning outcomes. This study is a quantitative study with an experimental method. The population is 50 students consisting of three classes. The sample is 50 students, with a sampling technique of total sampling. The data analysis technique used in this study is the t-test. Based on the calculation results obtained in the independent sample test, the sig-tailed: 0.000 is smaller than the significance level set at a = 0.05, which means that there is an influence on the results of learning PAI and Budi Pekerti students using the Everyone Is Teacher Here strategy (experiment) and using the expository strategy (control). And there is a significant influence of the implementation of the Everyone Is Teacher Here strategy on the results of learning PAI and Budi Pekerti students as seen from the paired t-test with the editors T1 pretest and T2 posttest which produces a sig value = 0.000 smaller than the significance level a = 0.05.